2021
DOI: 10.4103/ijoem.ijoem_101_19
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating hormone and free thyroxine alterations in subjects with occupational hearing loss

Abstract: Context and Aim: Occupational hearing loss (OHL) is caused by exposure to industrial noise. Alterations in the thyroid-stimulating hormone (TSH) and free thyroxine (FT4) levels are related to hearing loss. The purpose of this study is to investigate the TSH and FT4 level alterations in OHL. Methods and Material: Among 428 subjects, 144 male workers with normal hearing (NH), noise-induced hearing loss (NIHL), and high tone loss (HTL) (N = 48 in each group) were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…While there was no significant change in FT3 levels, FT4 levels were lower compared to single ionizing radiation-exposed and non-exposed workers. Epidemiological studies performed by Cioffi et al (2020) and Ranjbar et al (2021) have shown that workers exposed to low-dose ionizing radiation and patients with noise-induced hearing loss have lower FT4 levels than those without exposure and normal hearing, respectively (Cioffi et al 2020; Ranjbar et al 2021). Therefore, it is reasonable to infer that low-dose ionizing radiation and noise exposure may individually reduce FT4 levels, which may be superimposed when co-exposed.…”
Section: Discussionmentioning
confidence: 99%
“…While there was no significant change in FT3 levels, FT4 levels were lower compared to single ionizing radiation-exposed and non-exposed workers. Epidemiological studies performed by Cioffi et al (2020) and Ranjbar et al (2021) have shown that workers exposed to low-dose ionizing radiation and patients with noise-induced hearing loss have lower FT4 levels than those without exposure and normal hearing, respectively (Cioffi et al 2020; Ranjbar et al 2021). Therefore, it is reasonable to infer that low-dose ionizing radiation and noise exposure may individually reduce FT4 levels, which may be superimposed when co-exposed.…”
Section: Discussionmentioning
confidence: 99%